Precocious immunosenescence in HIV infection: effect of chronic viral persistence or antirretroviral therapy? (Research, Society and Development, 2020)
Antiretroviral therapies have increased the life expectancy of people living with HIV, however a major concern is the increase in comorbidities,  such as cardiovascular, metabolic bone and neurodegenerative diseases, which are the result of an immunosensitivity phenomenon associated with the cellular aging of the system immunological, called immunossenescence. This article aims to analyze the main factors promoting this event in HIV infection, discussing whether it is the result of chronic viral persistence or antiretroviral therapy. This is a review of the literature developed from consultation with the Virtual Health Library, using the MEDLINE and LILACS databases. The results showed that the HIV virus has the potential to influence the senescence of immune cells by reducing the number of CD4+ T lymphocytes, increasing CD8+ T lymphocytes, with shorter telomeres, and with a low rate of renewal due to deficiency in the production of its precursors. In addition, treatment with antiretrovirals also has the ability to accelerate the senescence of immune cells, either by the action of NRTIs on the enzyme telomerase or on the polymerase of mitochondria or by producing oxidative stress. Therefore, the evidence suggests that both processes can contribute to the accelerated establishment of a low-grade chronic inflammatory phenotype resulting in significant early immune remodeling in HIV infection.